Nepal Development Update, January 2016 : Development Amidst Disturbances - World Bank (World Bank, Washington, DC, 2016)
Devastating earthquakes in April and May of 2015 took a huge human toll, destroyed homes, businesses, irreplaceable cultural heritage sites, and slowed economic growth. The Government of Nepal (GoN), through a post disaster needs assessment (PDNA), estimated the value of losses at United States dollar (USD) 7.1 billion (physical damage of USD 5.2 billion and economic losses, spanning several years, of USD 1.9 billion). Nepal’s political parties intensified their efforts to adopt a new constitution, after eight years of deliberations, spurred on by the shift in political priorities following the April and May earthquakes. A normalization was envisaged whereby the faster budget implementation and sustained reconstruction activities can lead to a surge in imports, which will have tipped the current account balance into deficit over the forecast period, despite large remittances. Similarly, increased government spending on capital expenditure, as national reconstruction authority speeds up reconstruction activities, will lead to a larger budget deficit. The aim of this report is to report on key economic developments over the preceding months, placing them in a longer term and global perspective and to examine topics of particular policy significance.